The Implementation of Collaborative Writing to Develop the Ability to Write Hortatory Exposition Text at Senior High School - fatonatul hasanah; Jaftiyatur Rohaniyah; Ina Daril Hanna (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study was prompted by the low level of proficiency among students in writing hortatory exposition texts, particularly in organising ideas, constructing logical arguments, and using appropriate grammar and vocabulary. The aim of this study is to describe the implementation of collaborative writing in the teaching of hortatory exposition texts, to identify the challenges faced by teachers and students, and to analyse students’ responses to the application of this method at SMAN 4 Pamekasan. This study was prompted by the low level of proficiency among students in writing hortatory exposition texts, particularly in organizing ideas, constructing logical arguments, and using appropriate grammar and vocabulary. The aim of this study is to describe the implementation of collaborative writing in the teaching of hortatory exposition texts, to identify the challenges faced by teachers and students, and to analyse students’ responses to the application of this method at SMAN 4 Pamekasan. This study employs a qualitative approach using a case study design. Data sources were obtained from Year 11 teachers and students through observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and drawing conclusions using triangulation techniques to ensure data validity. The results of the study indicate that the implementation of collaborative writing was carried out through several stages, namely planning, drafting, revision, editing, and finalization in groups. This method proved capable of improving the quality of students’ writing in terms of text structure, idea development, and linguistic accuracy. Furthermore, collaborative writing also encourages active interaction, boosts learning motivation, and helps students to construct stronger arguments through discussion and peer feedback. However, there were several challenges, such as differences in students ‘abilities and uneven participation within groups. Overall, the study.